Prevalence, Awareness, Treatment, and Control of Hypertension among Adult Residents of Tehran: The Tehran Cohort Study. Issue 1 (11th May 2022) - Oraii, Alireza; Shafiee, Akbar; Jalali, Arash; Alaeddini, Farshid; Saadat, Soheil; Sadeghian, Saeed; Poorhosseini, Hamidreza; Boroumand, Mohamamdali; Karimi, Abbasali; Franco, Oscar H.
Background: High levels of blood pressure (BP) remain undetected and poorly controlled in large segments of the population leading to an enormous burden in terms of disease and mortality. Objective: We aimed to assess the prevalence, awareness, treatment, and control of hypertension in Tehran. Methods: We used the data of 8, 296 adults aged ≥35 years from the Tehran Cohort Study who were enrolled between May 2016 and February 2019. Hypertension was defined as systolic BP ≥140 mmHg and/or diastolic BP ≥90 mmHg, self-report, and/or current antihypertensive medication use. The age- and sex-weighted prevalence of hypertension and high normal BP was calculated using the 2016 national census. Furthermore, awareness, treatment, and control of hypertension were analyzed. Results: The mean age of the participants was 53.8 ±12.75 years, and 54.0% were women. The weighted prevalence of hypertension and high normal BP were 36.5% and 12.2%, respectively. Among hypertensive individuals, 68.2% were aware of hypertension, 53.3% were receiving medication, and 40.4% had adequate BP control. The awareness, treatment, and control of hypertension were significantly higher in women (72.2% vs. 63.4% [P < 0.001], 55.1% vs 51.1% [P = 0.020], and 42.7% vs. 37.7% [P = 0.004], respectively) and this gap considerably increased with advancing age. Hypertension was more prevalent in northern Tehran but with a better treatment rate and control in the same regions. Conclusion: Despite the high prevalence of hypertension in the adult population of Tehran, the rates of awareness, treatment, and control of hypertension are unsatisfactory and demand comprehensive strategies to improve this situation, especially in younger men.